N-(5-Amino-9H-benzo[a]phenoxazin-9-ylidene)propan-1-aminium chlorides as antifungal agents and NIR fluorescence probes - Sousa, Rui P. C. L. (2021)
The search for benzo[a]phenoxazines, Nile Blue derivatives, with high antifungal activity and cell labelling capacity based on our previously published works in this type of compounds, led us to the design of compounds with specific substituents in the polycyclic system. Thus, in the present work, four new benzo[a]phenoxazinium chlorides, possessing at the 5-position amino or (3-aminopropyl) amino groups and at the 9-position propylamino or dipropylamino groups, were synthesized. Another analogue, with (3-aminopropyl) amino group at 5-position, ethyl amino group at 9-position and a methyl group at 10-position of the polycyclic system was also synthesized for comparison in the studies performed. Fundamental photophysics (absorption and fluorescent emission) was carried out in absolute ethanol, water, and other aqueous solutions of different pH values, relevant for the potential biological applications of these compounds. The antiproliferative activity of the synthesized benzo[a]phenoxazinium chlorides was determined using Saccharomyces cerevisiae PYCC 4072 and the microdilution method described for antifungal susceptibility tests in yeast. All compounds revealed antifungal activity, being the most active the one possessing an amino group at 5-position and an aminopropyl group at 9-position. The potential as fluorescent probes were evaluated by fluorescence microscopy, using S. cerevisae as a model system of eukaryotic cells, and it was found that the benzo[a]phenoxazinium chlorides stained the cells with preferential accumulation that seems to appear at the vacuolar membrane and/or the perinuclear membrane of the endoplasmatic reticulum.